Effect of miR-223-3p on cell pyroptosis in myelodysplastic syndrome and its mechanism via regulating the expression of NLRP3 - Yin, Wanyi; Shen, Yang; Zhang, Lihong; Wang, Jianying; Yang, Liu; Liu, Qingchi (Cellular and Molecular Biology, 2022)
This study aimed to investigate the regulatory mechanism of the miR-223-3p/NLRP3 signaling axis in the progression of myelodysplastic syndrome (MDS). For this purpose, SKM-1 cells were transfected and three groups were set up according to different transfection protocols: si-NC group (NLRP3 silencing negative control plasmid), si-NLRP3 group (NLRP3 silencing plasmid), miR-223-3p mimic-NC group (miR-223-3p overexpressing negative control plasmid), miR-223-3p mimic group (miR-223-3p overexpressing plasmid), miR-223-3p mimic+oe-NLRP3 group and miR-223-3p mimic+oe-NLRP3 group (NLRP3 silencing combined with miR-223-3p overexpressing plasmid). Normal bone marrow cells were used as the control. qRT-PCR was used to detect relative expressions of NLRP3 and miR-223-3p; and Western blot to detect Ki67, Caspase-1, Gasdermin D, IL-1β, IL-18 and MMP-9 expressions. Cell proliferation detection used CCK-8 assay, cell cycle distribution detection adopted flow cytometry, and cell migration and invasion analyses relied on Transwell assay. Dual-luciferase reporter assay verified the relationship between NLRP3 and miR-223-3p. An animal experiment was finally conducted to confirm the results obtained in cells. Results showed that compared with normal bone marrow cells and K562 cells, there were significantly upregulated NLRP3 expression and upregulated expression of miR-223-3p in SKM-1 cells (all P<0.05). Compared with the si-NC group and mimic-NC group respectively, the si-NLRP3 group and miR-223-3p mimic group showed inhibited proliferation, blocked cells in the G0/M phase, reduced cells in S phase, inhibited cell invasion and migration, decreased expressions of Ki67, Caspase-1, Gasdermin D, IL-1β and IL-18, and MMP-9 (all P<0.05). NLRP3 was the direct target of miR-223-3p. Moreover, compared with the miR-223-3p mimic group, the miR-223-3p mimic+oe-NLRP3 group showed obviously increased expressions of NLRP3, Ki67, Caspase-1, Gasdermin D, IL-1β, IL-18 and MMP-9, promoted proliferation, invasion and migration, and increased cells in S phase (all P<0.05). The animal test revealed that compared with the mimic-NC+ oe-NC group, miR-223-3p mimic+ oe-NC group showed reduced tumor volume and decreased Ki67 expression (both P<0.05); while compared with miR-223-3p mimic+ oe-NC group, miR-223-3p mimic+ oe-NLRP3 group had increased tumor volume and increased Ki67 expression (both P<0.05). It was concluded that overexpression of miR-223-3p can effectively inhibit the expression of NLRP3 and cell pyroptosis in MDS.